Well-being and respect for seniors. Exploring the meaning of care farms - Frątczak-Muller, Joanna (Adult Education Discourses, 2025)
This article presents the process of establishing care farms in the Lubuskie Province of Poland, a model rarely implemented in the country until now. The study focuses on two key aspects: the mutual learning process of the team responsible for developing the operational principles of these care farms and the initial outcomes observed after a year of their operation. The research aims to understand how the self-learning process unfolded and to assess the impact of care farms on the wellbeing and respect of seniors, both in terms of self-respect and respect received from others. The study is guided by the theoretical frameworks of inclusive education and green care, with a focus on three core issues: respect and agency, social inclusion, and quality of life. Using a combination of document analysis and qualitative interviews with process implementers (team for developing a model of the operation of care farms in the Lubuskie Province) and participants of care farms, the findings reveal that the collaborative learning environment, enriched by direct exposure to green care practices and interactions with seniors during their daily activities, fostered a shared understanding and commitment to the project. This experience motivated the participants to adapt these practices to meet local needs, promoting respect and agency among seniors. The results suggest that seniors’ involvement in meaningful activities enhanced their self-esteem, sense of agency, and motivation, contributing to their overall well-being. The study concludes that care farms offer a promising model for elder care by enhancing both the external respect accorded to seniors and their internal self-respect, thereby supporting broader social inclusion goals and quality of life.